Financing real estate development using bonds in Asia - T. I. Lam, Patrick; Chiang, Yat Hung; H. Chan, Stephen (International Journal of Strategic Property Management, 2012)
During the global financial tsunami, banks were very cautious in financing business needs due to tight credit conditions. Alternative ways for financing projects were sought after by real estate developers worldwide. Within Asia, notably in Hong Kong SAR and Singapore, a number of reputable property developers have been tapping the capital debt market for funds in recent years amidst an increasingly regulated loan market and competitive pricing. In the face of a growing bond market, some corporate bond issues arranged by these property developers have been successful. Apart from investment appetite, property developers have to gauge carefully the pros and cons of raising funds through bond issues. Successful bond issues need to be structured with suitable credit enhancement features since the perception of risk and rising interest rates are major deterrents to potential investors who would otherwise face bond defaults or bear high opportunity costs with the committed funds. Through a number of case studies, the suitability of bond financing for property development is compared with loan financing. It is found that a close monitoring of market conditions and some foresight are essential ingredients for successful bond financing, for both straight bond issues and convertibles.First Publish Online: 11 Jan 2012